Internally fire protected composite steel-concrete slim-floor beam. (15th January 2021) - Albero, V.; Serra, E.; Espinós, A.; Romero, M.L.; Hospitaler, A.
Highlights: This work presents a slim-floor configuration which increases its fire protection. This new beam configuration is called "Internally Fire Protected Slim-Floor Beam". The IFP-SFB configuration is based on a new strategy that does not need maintenance. The IFP-SFB configuration results in up to 30–60 min of additional fire resistance. Abstract: The slim-floor beam is a composite concrete-steel beam fully integrated into the floor depth that was developed at the beginning of the 1990s. This composite beam presents a very good behaviour during the fire event because most of the steel parts of the section remain protected by the concrete encasement. Indeed, in a fire event, only the bottom surface of the lower steel plate results exposed to the heat source. The use of intumescent coating or other fireproof materials is the most common way to insulate the steel beam from fire but requires an accurate application and also appropriate maintenance during its whole life cycle to ensure proper fire protection. Thus, related to this last idea, the objective of this work is to present a new slim-floor configuration which increases the insulation of the beam from fire by using a design strategy that avoids the needed for maintenance. This new beam configuration has been called "Internally Fire Protected Slim-Floor Beam" (IFP-SFB) and implies a thermal break included within the beam cross-section. This paper presents the results of a series of thermal tests applied to this innovative slim-floor type proposed by the authors and its comparison against the most commonly used slim-floor configurations. Finally, the benefits of the proposed IFP-SFB configuration are presented, resulting in up to 30–60 min of additional fire resistance time. The IFP-SFB configuration is at present right-protected and under evaluation by the Spanish Office of Patents and Trademarks with reference number P201930438.